Market Linkages Between the US and Japan: An Application to the Fisheries Industry - Elston,Julie (Japan and the World Economy, 1999)
Recent trends in globalization of Pacific Basin commodity markets raises important questions concerning the nature of market integration and price linkages. This paper examines this issue by testing for price linkages between the United States and Japan for two species whose exports from the U.S. to Japan have risen considerably over the past decade. Empirical results indicate segmentation of price linkages for sablefish but probable price linkages for some thornyhead markets. Findings suggest that markets for these species may be less sensitive to price changes in Japan than would be expected based on commodity flows.
Keywords: Finance; OSU-Cascades